2019
DOI: 10.1101/656066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiome data enhances predictive models of lung function in people with cystic fibrosis

Abstract: The polymicrobial context of chronic infection has received increasing attention due to widespread use of microbiome sequencing technology. However, clinical microbiology analysis of infection samples in hospitals continues to focus only on established human pathogens. This disconnect between diverse ‘infection microbiomes’ and limited clinical microbiology profiling leaves open the possibility that important risk markers are being unexploited during infection management. To address this disconnect, we focus o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…and sputum inflammatory markers, such as neutrophil elastase, IL-8 and IL-1β in CF patients [66,67]. A recent report found the relative abundance of the genus Rothia in expectorated sputum to be a positive predictor of lung function in patients with CF [68]. Not only were we able to confirm a negative correlation between Rothia spp.…”
Section: Discussionsupporting
confidence: 63%
“…and sputum inflammatory markers, such as neutrophil elastase, IL-8 and IL-1β in CF patients [66,67]. A recent report found the relative abundance of the genus Rothia in expectorated sputum to be a positive predictor of lung function in patients with CF [68]. Not only were we able to confirm a negative correlation between Rothia spp.…”
Section: Discussionsupporting
confidence: 63%
“…2 ), indicating that Pa abundance can be considered as a proxy for lung microbiome diversity in our dataset. However, Shannon and Simpson diversity indices were not selected as predictive features in our model, consistent with a previous work (Acosta et al 2018; Zhao, Hao et al 2020). This suggests that, even if low microbiome diversity indices are associated with CF disease progression, the low diversity is likely driven by the dominance of key pathogens such as Pa .…”
Section: Resultsmentioning
confidence: 71%
“…2 ). Multiple studies have shown an association between poor lung function and low BMI (Snell, Bennetts et al 1998, Cystic Fibrosis Foundation 2006, Kumru, Emiralioğlu et al 2018), high abundance of Pa (Cox, Allgaier et al 2010) and age (Zhao, Hao et al 2020, Cox, Allgaier et al 2010). As expected, Pa relative abundance also showed a strong negative correlation with Shannon and Simpson microbiome diversity indices ( Supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations